Cannabinoid receptor 2 is necessary to induce toll‐like receptor‐mediated microglial activation. Issue 1 (9th September 2021) - Reusch, Nico; Ravichandran, Kishore Aravind; Olabiyi, Bolanle Fatimat; Komorowska‐Müller, Joanna Agnieszka; Hansen, Jan N.; Ulas, Thomas; Beyer, Marc; Zimmer, Andreas; Schmöle, Anne‐Caroline
Abstract: The tight regulation of microglia activity is key for precise responses to potential threats, while uncontrolled and exacerbated microglial activity is neurotoxic. Microglial toll‐like receptors (TLRs) are indispensable for sensing different types of assaults and triggering an innate immune response. Cannabinoid receptor 2 (CB2) signaling is a key pathway to control microglial homeostasis and activation, and its activation is connected to changes in microglial activity. We aimed to investigate how CB2 signaling impacts TLR‐mediated microglial activation. Here, we demonstrate that deletion of CB2 causes a dampened transcriptional response to prototypic TLR ligands in microglia. Loss of CB2 results in distinct microglial gene expression profiles, morphology, and activation. We show that the CB2‐mediated attenuation of TLR‐induced microglial activation is mainly p38 MAPK‐dependent. Taken together, we demonstrate that CB2 expression and signaling are necessary to fine‐tune TLR‐induced activation programs in microglia. Main Points: CB2 −/− microglia gene expression profile and changes in morphology after TLR stimulation are in line with a dampened microglial activation pattern. CB2 deletion alters TLR‐induced microglial activation via the p38 MAPK pathway.